Parental Education in Children’s Academic Performance - Bakar, Norsuhaily Abu; Ibrahim, Mudassir; Al-Smadi, Mohammad Shaban (International Journal of Psychosocial Rehabilitation, 2020)
This study proposes of how parenting education affects students' educational performance. The main goal of study is to analyze the impact of parental education and the educational qualifications of parents on the academic performance of high school students in Kuala Terengganu, Malaysia. It was used a descriptive survey where the data was collected from 200 participants using the self-management questionnaire from 4 chosen secondary schools in Kuala Terengganu design. Technique was used to take samples of a random stratified sampling of respondents. The data were analyzed using regression analysis. The findings are illustrated in three models; demographic information and analysis, descriptive and inferential analysis, the findings of analysis showed that the students of mothers and fathers who obtained a qualification highly educated are performing well compared to the performance of Parents with lower educational qualifications. Lastly, it makes recommendations to parents, educators, policymakers and educational leaders.